2011
DOI: 10.1063/1.3578446
|View full text |Cite
|
Sign up to set email alerts
|

Positron annihilation and relaxation dynamics from dielectric spectroscopy and nuclear magnetic resonance: Cis–trans-1,4-poly(butadiene)

Abstract: The electronic spectrum of SiH4: Jahn-Teller Rydberg series J. Chem. Phys. 135, 214304 (2011) Electronic states of tetrahydrofuran molecules studied by electron collisions J. Chem. Phys. 135, 134317 (2011) Dyson orbitals of N2O: Electron momentum spectroscopy and symmetry adapted cluster-configuration interaction calculations J. Chem. Phys. 134, 204304 (2011) Electronic excitations of potassium intercalated manganese phthalocyanine investigated by electron energy-loss spectroscopy J. Chem. Phys. 134, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 80 publications
(92 reference statements)
4
18
1
Order By: Relevance
“…In both cases, our data are in excellent agreement with previously reported PALS measurements for glycerol [42,47]. The observed temperature dependence of the o-Ps lifetime measured for bulk reflects the typical behaviour of molecular glass formers as they pass through their glass transition [43][44][45][46][47][48][49]. Three characteristic temperatures can be identified in the thermal response of τ − o Ps measured in bulk glycerol, which according to previously described notation can be identified as T g,PALS , T b with increasing temperature mirrors the thermal expansion of the local free volume in the glassy matrix due to the anharmonicity of the molecular vibrations.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In both cases, our data are in excellent agreement with previously reported PALS measurements for glycerol [42,47]. The observed temperature dependence of the o-Ps lifetime measured for bulk reflects the typical behaviour of molecular glass formers as they pass through their glass transition [43][44][45][46][47][48][49]. Three characteristic temperatures can be identified in the thermal response of τ − o Ps measured in bulk glycerol, which according to previously described notation can be identified as T g,PALS , T b with increasing temperature mirrors the thermal expansion of the local free volume in the glassy matrix due to the anharmonicity of the molecular vibrations.…”
Section: Resultssupporting
confidence: 92%
“…PALS is a well established technique extensively used for the study of local free volume and dynamics in a wide range of glass-forming systems, from simple liquids to synthetic polymers [37][38][39][40][41]. Over the past decade, PALS has been successfully used to study a variety of simple molecular glass formers both, in confinement [42] and in bulk [43][44][45][46][47][48][49]. Such studies have shown that model-free analysis of the temperature dependence of the orthopositronium (o-Ps) lifetime, τ − o Ps (reflecting the local free volume) reveals the existence of several characteristic temperatures [44,47,48].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the strength of a dipole is a very weak function of temperature and, thus, cannot account for the temperature dependence of the peak height in ε″(ω) response that would be similar to that seen in the G ″(ω) isotherms shown in Figure . Although the current study has not reported on the dielectric behavior due to parasitic conduction and electrode polarization effects (see the Supporting Information), similar dielectric effects are reported for many glass-forming materials, ,,,, which are also present for this DGEBA-MDA epoxy resins for temperature below T g that will be reported in a future publication.…”
Section: Discussionsupporting
confidence: 75%
“…Remarkably, T PALS is nearly the same as T B from dielectric and mechanical data of s a , as shown by the s 3 data as a function of temperature of three small molecular glassformers, ortho-terphenyl (OTP), propylene carbonate (PC), and glycerol, [64][65][66] and polymers. [67][68][69] The coincidence suggests that the crossover of T-dependence of s a at T B bears some connection to the corresponding change of T-dependence of free volume at or near the same temperature. The more rapid decrease in free volume with temperature on crossing T B from above implies the corresponding more rapid increase of intermolecular coupling, which is consistent with the observed change in the T- of the coupling parameter n(T) in eqn (4).…”
Section: Discussionmentioning
confidence: 86%